DEMNITATE, CONŞTIINŢĂ ŞI LIBERTATE RELIGIOASĂ ÎN CARTEA PROFETULUI DANIEL (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Dignity, Conscience and Religious Freedom in the Book of Daniel the ProphetThe book of Daniel is in the Old Testament of the Bible and is divided into two main parts: the story (chapters 1 to 6), and the prophecies (chapters 7 to 12). In the first part - the story - we find three particular situations in which the Religious freedom and the freedom of conscience is being challenged in the cases of few Hebrew men in a foreign country. From their experience which is recorded on the pages of the Holy Scriptures we can learn how to defend the human dignity, someone’s own dignity and the Religious freedom of every person.